Using text messaging services to enhance students' reading comprehension and critical thinking skills - Zamnah Husin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The objective of this study was to investigate the effects of the mobile phone text messaging facility (SMS) on students' reading comprehension and critical thinking skills. Six hundred and fifty-one (651) local and international students from the International Islamic University Malaysia (HUM) were involved in this study. They were taking the various English language proficiency courses from lower to intermediate levels namely LE 0225 (English Language II), LE 0320 (English Language III). LE 0420 (English Language IV), LE 0520 (English Language V), LE 0620 (English Language VI). The students were divided into two groups consisting of 438 students in the experimental groups and 213 students in the control groups. Students in the experimental groups were exposed to the SMS reading activity. Reading comprehension texts, comprehension questions, and answers were sent to their mobile phones for approximately 3 months. Students in the control groups were not exposed to this kind of activity. Standardised reading comprehension test prepared by the Centre for Languages and Pre-University Academic Development (CELPAD) at IIUM and Cornell Critical Thinking Test (Level X) were administered before and after treatment to measure students' development in reading comprehension and critical thinking skills. A questionnaire survey was administered at the beginning of the study to find out students' demographic characteristics and their mobile phone usage. Students' comments and feedback on the SMS reading activity were obtained at the end of the treatment via interviews and emails. The findings revealed that students in the experimental groups improved significantly in reading comprehension compared to the control groups. The findings also revealed that the students improved significantly in critical thinking and the sub-skills of critical thinking, The findings based on students' comments and feedback revealed that they enjoyed the activity and felt they had improved in reading comprehension, critical thinking, vocabulary. writing, speaking, and figurative language. The study suggests there is a potential in adopting mobile devices namely mobile phones to complement classroom learning.